Perhitungan Kapasitas Sump Pit 4 PT RPP Contractors Indonesia Job Site PT Adimitra Baratama Nusantara Provinsi Kalimantan Timur: Penentuan Kapasitas Sump - Bahnan, alfida (Institut Teknologi Nasional Yogyakarta, 2024)
Coal mining activities carried out by PT RPP Contractors Indonesia Job Site PT Adimitra Baratama Nusantara use the open pit method which causes the opening of a large basin so that it has the potential to become a water storage area, both from surface runoff and groundwater. Mine Dewatering is an effort to remove water that has entered the mining area, the way to handle this is by making a sump. This research aims to determine the total water discharge or volume of water entering the sump so that the sump capacity can be calculated. The study methods are hydrology, groundwater, provisions according to regulations, and draining. Based on the calculation results, the sump volume is 371,347.20 m3, the sump capacity is 464,184.00 m3, with a depth of 12 m, the sump pit 4 area is 38,682 m2.